Case of familial interstitial lung disease attributed to ATP-binding cassette transporter 3 gene mutation in identical twins - Tsuchiya, Kazuo; Nakamura, Yutaro; Setoguchi, Yasuhiro; Matsushima, Sayomi; Iwaizumi, Moriya; Inoue, Yusuke; Yasui, Hideki; Hozumi, Hironao; Karayama, Masato; Suzuki, Yuzo; Furuhashi, Kazuki; Enomoto, Noriyuki; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Mutations in ABCA3 can result in surfactant deficiency, leading to respiratory distress syndrome in term neonates, and interstitial lung disease (ILD) in children. Here, we report an extremely rare case of ILD in an identical twin with novel ABCA3 germline mutations. Interestingly, they showed mostly similar, but slightly different, clinical features. Our cases suggest that, in addition to genetic factors, non-genetic factors are involved in the severity of the disease and its clinical course. Studies of gene-environment interactions, especially with twins, are needed, as they may contribute to the understanding of the clinical heterogeneity of ILD and its association with various underlying conditions as well as rare variant mutations.